(untitled) (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Ageing is a normal phenomenon. Various studies shows that there is a sharp rise in the elderly population in the last few years. Prevalence of depression in elderly is found to around 13% in the community sample in various countries. There is a dearth of study related to psychiatric illness in elderly in Nepal. This study was aimed to find the prevalence of depression in elderly and see for various factors associated with elderly depression. Material And Method: This was a cross-sectional study conducted at Siddharthnagar Municipality, Bhairahawa, Rupandehi. 316 elderly were selected by using systematic random sampling technique. A Semi- structured interview schedule was developed to collect Socio-demographic data. The Short Form Geriatric Depression Scale (SF-GDS) was used to find out the prevalence of depression among elderly people. Ethical Approval was obtained from the Institutional Review Committee, Chitwan Medical College and permission was obtained from Siddharthnagar Municipality, Bhairahawa, Rupandehi. The collected data was entered in Epidata 3.1 and the data was exported and analyzed in IBM SPSS 20. Results: There were a total of 316 samples in this study. The mean age of respondents was 68.47 years of age. Majority of the respondents (54.1%) were female and living in joint Family (72.2%). Almost 45.9% respondents were from upper caste groups, 90.5% of respondents were Hindus. Among the married (100%) respondents, 54.6% of respondents were living with spouse and 3.2% were divorced and separated from spouse. Depression was present in 49.4% of respondents were depressed. Among depressed respondents, 46.7% of respondents were having mild depression, 39.2% moderate depression and 14.1% severe depression. Conclusion: The finding of this study concluded that depression among elderly people was a substantial problem in Siddharthnagar Municipality, Bhairahawa, Rupandehi.